ANALYSIS EFFECT OF CONFLICT ROLE, SOCIAL SUPPORT TO ORGANIZATIONAL COMMITMENT AND IMPACT ON INTENTION TO QUIT - Najib, M. Fajar Chilman (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2018)
Human resources (HR) is the only important organizational asset that can drive other resources. Human resources can affect the efficiency and effectiveness of the organization (Simamora, 2006). Secondary data in this research are: Data obtained from the management of PT. Bank Syariah Mandiri in the form of data turnover. Population in this research is employees of PT. Bank Syariah Mandiri Semarang, Jl. Pandanaran no. 90 a total of 137 employees. The method of collecting primary data is done by using documentation technique. Role conflict has a significant effect on the intention to quit. It is concluded that the greater the role conflict increases the intention to quit. The result of hypothesis 2 testing showing the role conflict has a positive effect on intention to quit is accepted, where high conflict can increase the intention to exit.Organizational support has a significant positive effect on commitment. It is concluded that the greater the support the organization increases its commitment. Organizational support has a significant negative impact on intention to quit. It is concluded that greater organizational support decreases the intention to quit. Commitment has a significant negative effect on intention to quit. It is concluded that the stronger the commitment can decrease the intention to quit.